A new species of the genus Xenophrys (Amphibia: Anura: Megophryidae) from an offshore island in Guangdong Province, southeastern China - Wang, Jian; Liu, Zu-Yao; Lyu, Zhi-Tong; Zeng, Zhao-Chi; Wang, Ying-Yong (Zootaxa, 2017)
A new species, Xenophrys insularis sp. nov., is described based on a series of specimens collected from Nan’ao Island, Shantou City, Guangdong Province, China. The new species is a separately evolving lineage that was robustly supported by the phylogenetic analysis based on the mitochondrial CO1 + 12S rRNA + 16S rRNA genes; morphologically, it can be distinguished from other known congeners by the following combination of characteristics: body size moderate, SVL 38.6–41.2 mm in adult males, 47.1 mm in a single adult female; snout obtusely rounded in dorsal view; head width slightly larger than head length; strong vomerine ridge bearing vomerine teeth; margin of tongue weakly notched behind; supratympanic fold forming a large swollen supraaxillary gland above insertion of arm; hindlimbs relatively short, heels not meeting when thighs are held at right angles to body, tibio-tarsal articulation reaches forward the posterior edge of tympanum; fingers and toes without lateral fringes, with rudiment of web at bases of toes, distinct subarticular tubercle only at the base of each finger and toe; single vocal sac in males; gravid female bears pure white oocytes. Xenophrys insularis sp. nov. is endemic to the Nan’ao Island and represents the first Xenophrys species found on and possibly endemic to a small offshore island.